A study of the air and sea surface temperatures over the Indian Ocean (MAUSAM, 1980)
Several studies on the air and sea surface temperatures over Indian Ocean : particularly over west Arabian Sea have been reported (Verploegh 1960; Colon 1964; Bunker 1965; 1970, 1974; Shukla 1975, 1977).The present paper is a study of the air and sea surface temperatures over the Arabian Sea and Bay of Bengal during the seven year period 1961 to 1967. Its purpose is to demarcate, with the recent date, Indian Ocean into separate zones each of a particular character with reference to the variation of the air and sea surface temperatures through the year as also the warmer than air-sea and colder than air-sea conditions during the southwest monsoon season. An attempt to examine the association of the anomalies of sea surface temperatures over the Arabian Sea to the variation in the activity of monsoon over India in the respective years has also been made.